Acupuncture points can be identified as cutaneous neurogenic inflammatory spots. Issue 1 (December 2017) - Kim, Do-Hee; Ryu, Yeonhee; Hahm, Dae; Sohn, Boo; Shim, Insop; Kwon, O.; Chang, Suchan; Gwak, Young; Kim, Min; Kim, Jae; Lee, Bong; Jang, Eun; et al.
Abstract Acupuncture, a traditional medical procedure practised for over 2000 years in Asia, stimulates specific but poorly defined sites called acupoints. To date, no unique anatomical acupoint structures have been found. However, noxious sensory signals from visceral organs produce hypersensitive spots on the skin (neurogenic spots), caused by cutaneous neurogenic inflammation, in the dermatome that overlaps with visceral afferent innervations. Here, we show that an acupoint is one form of neurogenic inflammation on the skin. Various studies have demonstrated that acupoints show mechanical hypersensitivity and have high electrical conductance. Stimulation of acupoints produces needling sensations caused by the activation of small diameter afferent nerve fibres and therapeutic effects on the associated visceral organs, which is likely due to the release of endogenous opioids. The present study provides experimental evidence that neurogenic spots exhibit all the characteristics of the acupoints listed above. In addition, the stimulation of neurogenic spots by electrical, mechanical, or chemical means alleviated pathological conditions in rat colitis and hypertension models via the endogenous opioid system. Our results suggest that acupoints associated with internal organs may be identical to neurogenic inflammatory spots on the skin, which are produced by activation of somatic afferents in abnormal conditions of visceral organs.